Enhancing Students’ Motivation in Learning English Grammar Through A Computer-Supported Learning Classroom Management - Bahruddin (JEELS (Journal of English Education and Linguistics Studies), 2015)
This research is to examine the students‘ motivational factors and attitude towards the learning of English grammar in a Computer supported Learning System. Twenty-nine students were taught with a student-centered approach and three grammar learning web sites were used frequently for classroom and individual English grammar practice, whereas another twenty-nine were taught with the traditional teachercentered approach. Both groups were given grammar correction and explanation tests before and after the study. After comparing the results of the pre-test and post-test with those of the control group, it was found that the experimental group excelled over the control group in both grammar correction and grammar explanation. It proved that students‘ implicit and explicit knowledge on English grammar was greatly improved by the computer-supported teaching methods and environment. Further interviews with the students also revealed that the new pedagogical practice had provided many positive motivational factors in supporting students‘ learning process.